2019
DOI: 10.15408/tazkiya.v22i1.8165
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Work Family Conflict, Modalpsikologis Dan Variabel Demografis Terhadap Kinerja Guru

Abstract: This study aims to examine the effect of work family conflict, psychological capital and demographic variables on the performance of 200 teachers. Sampling conducted using non probability sampling technique. Measurers used in this study consist of Individual Work Performance (IWP) to measure performance, then the authors make their own items to measure work family conflict and use Psychological Capital Questionnaire (PCQ-24) to measure psychological capital. Test the validity of measuring instruments using Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Dalam tinjauan kinerja guru, konflik moral pada guru harus diketahui faktor internal dan eksternal yang mempengaruhinya. Agar tidak berakibat negatif terhadap proses pembelajaran (Nashtya & Baidun, 2019) yang diselenggarakan. Guru, peserta didik, orang tua, dan kepala sekolah memiliki pandangan moral masing-masing tentang tentang keputusan dan tindakan yang benar untuk dilakukan.…”
Section: Pendahuluanunclassified
“…Dalam tinjauan kinerja guru, konflik moral pada guru harus diketahui faktor internal dan eksternal yang mempengaruhinya. Agar tidak berakibat negatif terhadap proses pembelajaran (Nashtya & Baidun, 2019) yang diselenggarakan. Guru, peserta didik, orang tua, dan kepala sekolah memiliki pandangan moral masing-masing tentang tentang keputusan dan tindakan yang benar untuk dilakukan.…”
Section: Pendahuluanunclassified
“…Namun jika pengaturan resiliensi dalam diri seorang guru sudah tergolong tinggi maka kinerja guru tersebut juga akan maksimal. Sejalan dengan penelitian terdahulu yang menyatakan bahwa resiliensi memiliki pengaruh yang signifikan terhadap kinerja guru (Nashtya & Baidun, 2018). Seseorang dengan resiliensi tinggi akan berusaha untuk terus memperbaiki diri dan berusaha agar masalah yang ada dapat diatasi sehingga tidak berdampak bagi pekerjaannya.…”
Section: Pembahasanunclassified
“…In their research, Nashtya & Baidun (2017) concluded that a teacher that has good psychological capital will have spirit and effort to reach the goal and it is actualized with good performance over time. Whereas, according Luthans et al (2007) a teacher that has good psychological capital (PsyCap), self efficacy (optimism, hope, resilience) will resulted on teacher's high performance.…”
Section: Introductionmentioning
confidence: 99%